ROUNDABOUTS IN JAPAN – SURVEYING, PROBLEMS AND ISSUES - Elżbieta MACIOSZEK (Scientific Journal of Silesian University of Technology. Series Transport)
A roundabout is not a popular intersection type in Japan. Vehicular traffic at most road crossings are controlled by traffic lights. This article comments upon a survey of Japanese roundabouts along with their numerical characteristics concerning, among other aspects, the location of roundabouts in specific areas where the surrounding is managed in different ways (that is, urban area, suburban area, residential area, etc.). Moreso, the location of roundabouts in specific regions and prefectures, classification of roundabouts according to the number of legs, outer diameter, etc. The survey in question was conducted as part of a project entitled “Analysis of the applicability of the author's method of roundabouts entry capacity calculation developed for the conditions prevailing in Poland to the conditions prevailing at roundabouts in Tokyo (Japan) and in the Tokyo surroundings” financed by the Polish National Agency for Academic Exchange.